Technology in Psychology Graduate Training Clinics: Past, Present, and Future - Hersh, Jacqueline; Thompson, Sarah M.; Farmer, Ryan; Keenan-Miller, Danielle (Journal of technology in behavioral science, 2024)
University-based training clinics serve two complementary functions: (1) offering high-quality training in the provision of behavioral health services to graduate trainees in health service psychology and related disciplines and (2) serving the local community by providing accessible, effective mental health treatment. Importantly, increasing access to mental healthcare for underserved and unserved populations by offering low-cost or free services has been a major goal of university training clinics from their inception. The limitations to in-person services during the COVID-19 pandemic coupled with increased emphasis on the social justice mission of training clinics have profoundly shifted graduate mental health training. The present paper summarizes the results of a voluntary survey completed by 110 members of the Association of Psychology Training Clinics in Winter 2023. Results indicate a significant shift in the current (95.7%) and anticipated future use (98.9%) of telehealth in graduate training clinics compared to 2019 (8.3%). Descriptive data highlight the integration of technology into all aspects of psychology training, including the use of electronic health records, routine outcome monitoring, telepsychology, and telesupervision. Characteristics of training clinics associated with the utilization of technology in training are also explored. Together, these data suggest that graduate training in behavioral health has undergone a profound shift toward increased use of technology, hopefully facilitating increased access to mental healthcare for underserved and unserved populations.